Hobo jungle: a homeless community in Paradise - Wakin, Michele (Lynne Rienner Publishers, 2020)
"For many decades and for many reasons, people who are homeless have chosen to live in camps or other makeshift settings, even when shelters are available. Is this an act of resistance? Of self-preservation? Or are they simply too addicted, too mentally ill, or too criminal to adapt to the rules and regulations of shelter life? To address these questions, Michele Wakin explores the evolution of unsheltered homelessness through an evocative portrait of a jungle encampment that has endured since the Great Depression in one of the most opulent cities on California's south coast"--